SUCCESS RATES OF TAMSULOSIN AND DUTASTERIDE AS MEDICAL THERAPY BASED ON IPSS IN SYMPTOMATIC BPH PATIENTS IN ARIFIN ACHMAD HOSPITAL PEKANBARU RIAU - Zamzami, Zuhirman (Indonesian Urological Association, 2018)
Objective: To evaluate the success rates of tamsulosin and dutasteride as medical therapy based on international prostate symptom score (IPSS) in symptomatic benign prostatic hyperplasia (BPH) patients. Materials & Methods: We reviewed medical records of the symptomatic BPH patients in Arifin Achmad Regional General Hospital, Pekanbaru, Riau Province, Indonesia in 2011-2016. The previous and after IPSS of administering tamsulosin 0.2 mg or 0.4 mg or dutasteride 0.5 mg as a single therapy and tamsulosin 0.4 mg with dutasteride 0.5 mg as a combination therapy were assessed. Wilcoxon test was used for statistical analysis. Approval on the study was obtained from the Ethical Review Board for Medicine and Health Research, Medical Faculty, University of Riau. Results: 100 patients fulfilled the inclusion criteria. The results showed 50% patients with mild IPSS and 50% patients with severe IPSS before the medication. 70% patients administered tamsulosin 0.2 mg as first-line therapy, 35% patients administered medication for 6 months-1 year, and 3% patients with mild IPSS, 44% with moderate IPSS and 53% with severe IPSS after the medication. The Wilcoxon test showed there was a significant different (p<0.005) between IPSS levels before and after the medication with success rate 18%. Conclusion: There were good success rate of tamsulosin 0.2 mg, tamsulosin 0.4 mg, dutasteride 0.5 mg as single therapy and tamsulosin 0.4 mg with dutasteride 0.5 mg as combination therapy in symptomatic BPH patients based on IPSS, and the medical therapy are still recommended.